2010
DOI: 10.1159/000314812
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Kidney Function Estimated by Cystatin C and Clinical Outcomes in Hypertensive Patients with Coronary Artery Disease: Association with Homocysteine and Other Cardiovascular Risk Factors

Abstract: Aims: To evaluate the association between serum cystatin C and homocysteine concentrations, cardiovascular risk factors and cardiovascular events in hypertensive patients with coronary artery disease (CAD). Methods: 260 patients with hypertension and CAD (mean age 56.9 ± 9.3) were included. During a mean 40-month follow-up the combined end-point of death from all causes, non-fatal myocardial infarction and stroke or coronary revascularization was assessed. Results: Subjects in the highest serum cystatin C quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Increased cystatin C levels are associated with carotid IMT in a multi-ethnic study on atherosclerosis [ 24 ], in the general population [ 23 ], in the health check-up population [ 20 ], in postmenopausal women [ 21 ], in metabolic syndrome patients [ 19 ], in patients with hypertension [ 16 , 17 , 25 ], and in patients with type 2 diabetes [ 26 , 41 ]. By contrast, a study investigated 446 Japanese adults without chronic kidney disease and proteinuria and did not find the relationship of cystatin C and carotid IMT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased cystatin C levels are associated with carotid IMT in a multi-ethnic study on atherosclerosis [ 24 ], in the general population [ 23 ], in the health check-up population [ 20 ], in postmenopausal women [ 21 ], in metabolic syndrome patients [ 19 ], in patients with hypertension [ 16 , 17 , 25 ], and in patients with type 2 diabetes [ 26 , 41 ]. By contrast, a study investigated 446 Japanese adults without chronic kidney disease and proteinuria and did not find the relationship of cystatin C and carotid IMT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…46 Diabetes and diet have also been shown to alter the gut microbiome, but there has been no causal relationship described between altered microbiome and risk of obesity and diabetes owing to confounding human factors. 47 The importance of symbiotic microbial community is undeniable.…”
Section: Modifiable Maternal Factors Altering the Fetal Epigenome In mentioning
confidence: 99%
“…In addition, in hypertensive patients with coronary heart disease, Cys C is associated with severity of coronary artery disease, homocysteine levels in plasma and traditional risk factors. It was also found that Cys C serves not only a marker of renal dysfunction but also a marker of chronic inflammation in patients with hypertension [17,18,37,38].…”
mentioning
confidence: 99%
“…Cys C is freely filtered in glomerular capillaries, and since its molecule is not exposed to either tubular reabsorption or secretion, it can be considered almost a perfect marker of gFr. The concentration of Cys C in serum should be inversely related to the size of the gFr since when it enters the tubular space during reabsorption, Cys C is almost completely metabolized in the proximal convulsive tubule [14,18,20].…”
mentioning
confidence: 99%